The Effect of Green Betel Leaf Water Bath on the Healing Time of Perineal Wounds in Postpartum Mothers in the Work Area of the Sikui Community Health Center - Rima Puspita Dewi; Reny Retnaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Perineal wounds are a common condition experienced by postpartum mothers after vaginal delivery and can potentially cause pain, discomfort, and the risk of infection if not properly cared for. Effective, safe, and culturally appropriate perineal wound care is a crucial need in postpartum care, especially at the primary health care level. Green betel leaves (Piper betle L.) are known to have antiseptic and anti-inflammatory properties that have the potential to support the wound healing process. This study aims to analyze the effect of green betel leaf water baths on the perineal wound healing process in postpartum mothers in the Sikui Community Health Center (UPT) work area. This study used a quantitative quasi-experimental design with a one-group pretest–posttest approach. The study was conducted in June–July 2025 with 18 postpartum mothers with grade I and II perineal wounds as respondents. Wound condition assessment before intervention was carried out using the REEDA instrument as a baseline condition, while healing results were evaluated based on clinical outcomes and the duration of perineal wound healing. Data analysis was conducted descriptively. The results showed that all respondents experienced clinical perineal wound healing after the green betel leaf water bath intervention. The majority of postpartum mothers experienced wound healing in less than one week, with a median healing time of 5.5 days. In conclusion, green betel leaf water bath has the potential to support the perineal wound healing process in postpartum mothers. This intervention can be considered a safe, easy-to-implement, and relevant complementary therapy for integration into postpartum care in primary healthcare settings.